Analysis of Factors Influencing the Number of Inpatient Visits at Catharina 1914 General Hospital Range - Sari, Ratu Novita; Rohendi, A.; Mardiyanto, Mochamad Sukrisno (Research of Service Administration Health and Sains Healthys, 2025)
Hospitals are one type of individual health care facility that is a very important health resource for carrying out health efforts. The development and growth of the increasing number of hospitals have given the public many choices. One of the services that can be chosen by the public is inpatient care. The behavior of customers/consumers in making decisions to choose health care facilities in hospitals is influenced by several factors/components. The higher the decision- making made by consumers in a hospital, the more it will affect many things, such as increasing hospital profits, thus ensuring the sustainability of the hospital and improving the quality of the hospital. The purpose of this study was to determine the factors that influence the number of inpatient visits at General Hospital Catharina 1914 Kisaran. This type of research is quantitative research. Data were obtained from 180 respondents who were inpatients. Data processing with the Classical Assumption Test using the assistance of the Statistical Package For The Social Science (SPSS). From the results of the study, it was partially known that the factors influencing the number of inpatient visits were the service of the officers as well as the location and accessibility. Meanwhile, it is known simultaneously that the service of officers, facilities, costs, location and accessibility have a simultaneous effect on the number of visits by inpatients at General Hospital Catharina 1914 Kisaran.